Relationship between the Reliability of Tennis-Specific Change of Direction (77COD) Test and Squat Jump–Countermovement Jump in Adolescent Tennis Players - Selman Kaya; Aysu Önal; Gökhan Deliceoğlu (Applied Sciences)
The aim of this study was to investigate the reliability of the tennis-specific change of direction (77COD) test with vertical jump tests (Squat Jump and Countermovement Jump) in adolescent tennis players. A total of 58 athletes (31 girls, 27 boys) actively playing tennis, with an average age of 10.57 ± 2.54 years, participated in the study. Tests and retests were completed within 2 weeks. Bland–Altman (B&A) plots were established and Pearson’s correlation analysis was conducted on the 77COD, CMJ, and SJ tests. Simple linear regression analysis (enter method) was used to determine the significant predictors of the 77COD variable from the SJ-CMJ variables. The SJ and CMJ were found to be highly negatively correlated with the 77COD test (−0.72 ≤ r ≤ −0.74). The test–retest reliability of the 77COD test was found to be very high, with an intraclass correlation coefficient (ICC) of 0.95. Our findings showed that the 77COD test is suitable for determining COD ability in adolescent tennis players. In addition, vertical jump heights are an informative and practical performance indicator for 77COD. In conclusion, the 77COD test is a COD test that can be used in coaching practices without the need for complex testing materials.